The Bright Side of COVID-19: Integrated Art-based and Virtual Learning in Medical Education - Afsaneh Yakhforoshha; Fatemeh SamieeRad (Iranian Society of Pathology, 2021)
This approach to learning is in accordance with the first of six strategies of Harden SPICES model for curriculum development: student-centered against teacher-centered approach (S) (7,8). In total, the results from medical students and the Knowles' Andragogical Model as a theoretical lens, is expected to help medical education experts with emphasizing student center approach in the medical education curriculum to prepare future physician for meeting unexpected healthcare crisis demands.